Did Thracian influences extend into Christianity - Hoddinott, Ralf F. (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of the influence of Thracian religion on the development of early Christianity. The aim of the work is to assess the scope of these influences and to identify syncretic elements. The author applies historical-religious and comparative analysis. The most important results indicate that Thracian religion, especially the cult of the Thracian Rider, could have influenced Christianity through syncretic processes. An example is the identification of the Rider’s image with the figure of St George and the functioning of former sanctuaries as places of Christian worship. The author also points to ideological similarities, such as monotheism and belief in life after death, which could have facilitated the reception of Christianity. The conclusion is the hypothesis of a significant, although difficult to prove unequivocally, contribution of Thracian traditions to the formation of Christianity.